2015
DOI: 10.4168/aair.2015.7.3.221
|View full text |Cite
|
Sign up to set email alerts
|

Specific Immunotherapy in Atopic Dermatitis

Abstract: Allergen specific immunotherapy (SIT) using house dust mite (HDM) extracts has been performed mainly with patients of asthma and allergic rhinitis. In the meanwhile, there has been a long debate on the efficacy of SIT in atopic dermatitis (AD) with only a few double-blind placebo-controlled trials. However, several randomized controlled trials of SIT in AD revealed significant improvement of clinical symptoms and also, positive result was shown by a following meta-analysis study of these trials. In order to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 95 publications
0
41
0
Order By: Relevance
“…Sensitization to house dust mites was confirmed in these patients, and allergen-specific immunotherapy was proved to be effective, with 92.7% of the patients showing improvement of pruritus and 45% of the patients achieving remission. Only 16% of the patients showed either minimal improvement or no change 4447. Its safety was also proved, with only 0.1% of systemic adverse effects, such as flu-like symptoms, observed in our institution.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Sensitization to house dust mites was confirmed in these patients, and allergen-specific immunotherapy was proved to be effective, with 92.7% of the patients showing improvement of pruritus and 45% of the patients achieving remission. Only 16% of the patients showed either minimal improvement or no change 4447. Its safety was also proved, with only 0.1% of systemic adverse effects, such as flu-like symptoms, observed in our institution.…”
Section: Discussionmentioning
confidence: 53%
“…Patients with AD are frequently sensitized to house dust mites, and several recent, reports have shown that allergen-specific immunotherapy is a safe and efficacious treatment 444546. At our facility, allergen-specific immunotherapy is recommended to patients with the extrinsic type of AD showing severe symptoms and experiencing frequent flare-ups, to those unresponsive to conventional treatments, and to those who were able to regularly follow the schedules.…”
Section: Discussionmentioning
confidence: 99%
“…SIT is well established as the modality which has been proven in controlled prospective studies and is currently used in the management of allergic rhinitis, allergic asthma, and venom allergy . In atopic dermatitis (AD), SIT has been recently supported by a randomized controlled trial and meta‐analysis, especially in patients sensitized with house dust mite allergen . The mechanisms of how SIT ameliorates allergic reactions are not completely understood, but peripheral T‐cell tolerance is thought to play an important role .…”
Section: Introductionmentioning
confidence: 99%
“…Etiology and pathogenesis of AD is complex and multifactorial, and its clinical manifestations result from an interaction of genetic and environmental factors . Patients with AD have an impaired skin barrier that leads to dry skin due to increased transepidermal water loss, higher risk of skin infections, and penetration of allergens through an abnormal stratum corneum . These allergens can activate a local immune response by interacting with effector immune cells in the skin, and due to the local inflammatory cytokine milieu and atopic predisposition of patients, promote a Th2‐skewed activation of T cells that drives IgE‐mediated sensitization …”
Section: Introductionmentioning
confidence: 99%